“Please, Sir, I Want Some More.”: (A Case Study of Child Mortality of Palghar District, State of Maharashtra, India, from August 2014 – October 2016) - Matkar, Sharmishtha L. (European Scientific Journal, ESJ, 2017)
This study examines the relationship between climate change and undernourishment and its negative impact on child health. The focus of this study is Palghar District (which was formed on August 1, 2014, in State of Maharashtra, India). This paper examines the efficacy of the role of healthy government initiatives and their awareness among people in overcoming the adverse effects of climate-change. The study is based on interviews with the District Collector, various government officials and anthropologists working in the area, as well as secondary data collected from the Palghar District Collectorate. As the data made available by the government were limited, the study is unable to supply extensive information about such aspects as the beneficiaries of various welfare schemes, project costs and cost analysis. Palghar district has reported 64 per 1000 child deaths and 44 per 1000 infant deaths between April and October, 2016. The researcher tried to find links between various potential variables and child mortality in this administrative region. The researcher hopes that by giving voice to a localised issue and discussing possible solutions for curbing the problem of child mortality due to undernourishment, it may be possible to find a long-term and comprehensive model for a solution for the same problem around the world.